RESPONSE OF BEDE GRASS (Brachiaria decumbens) PRODUCTION DUE TO DEKAMON HORMONE TREATMENT IN VARIOUS SPRAYING FREQUENCY OF GANDASIL D - Sawen, Diana; Muin, M. Aff’an; Susilowati, . (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 9 No 2 (2020): Pastura Vol. 9 No. 2 Tahun 2020DO - 10.24843/Pastura.2020.v09.i02.p01, 2020)
This study aims to determine the dosage of dekamon as the appropriate growth regulators at various frequencies spraying foliar fertilizer for grass Brachiaria decumbens production. The study was conducted for 4.5 months housed in the Central Animal Breeding and Forage Animal Feed (BPT-HMT) Department of Animal Husbandry and Animal Health in West Papua Province at Sumber Boga villages Masni District of Manokwari regency, while the analysis of dry matter in the Laboratory of Animal Nutrition and Feed, Faculty of Animal Husbandry the State of Papua University Manokwari. The method used is the method of experimental design completely randomized design (CRD) with two treatments. Treatment dekamon (D) with 6 levels is D0 (without administration), D1 = 0.4 ml/250 ml of water, D2 = 0.5 ml/250 ml of water, D3 = 0.6 ml/250 ml of water, D4 = 0.7 ml/250 ml of water and D5 = 0.8 ml/250 ml of water. Each stage treatment was repeated 5 times so that there are 30 units of the experiment. Furthermore, using 3 experimental plots with a size of 2.4 x 2 m 2 / plot for the treatment of foliar fertilizer spraying frequency with Gandasil D, each plot I (S0) for no spraying, plot II (S1) for spraying 1 times/week and plot III (S2) for spraying 2 times/week. Data were statistically analyzed and the difference between the levels of a certain treatment were analyzed by t-test. Results of this study showed that administration of dekamon as growth regulators did not affect the growing of Bede grass, but the frequency of spraying foliar fertilizer 2 times/ week very significant effect on the number of tiller in a dosage dekamon 0 ml and 0.6 ml. Dekamon proper dosage for growing of Bede grass is without dekamon with spraying frequency of 2 times/week. Keywords: Brachiaria decumbens, production, dekamon, D gandasil fertilizer